Prospects for capital formation and capital markets : financial requirements over the next decade - Sametz, Arnold W. (Lexington, Mass. : Lexington Books, 1978)
This volume brings together analysis of and forecasts for the key sectors of the financial environment over the next decade and presents an economy-wide forecast in the traditional Federal Reserve System format
Includes bibliographical references and index.
osc 9/11/17
Loans
Keywords: Saving and investment; Flow of funds; Finance